Americans' Downward Mobility Shifts Votes to the Right - Ghilarducci, Teresa; Tursini, Ludovica (Social research, 2024)
A decline in a person's economic security relative to that of their relatives, neighbors, and any other group used by people in comparing themselves is correlated with emotional states of loss, anger, anxiety, and decline in subjective well-being. Using publicly available data on voting patterns for 910 selected counties in the United States in four presidential election cycles (2008, 2012, 2016, and 2020), we find that if people in a county experience downward mobility in relative economic security, the county that was once majority Democratic would likely shift to majority Republican voting. This evidence suggests that the fear of loss of relative economic security is associated with voting for authoritarian candidates and agendas.